The most brilliant boldly going book of exploration ever by the Brainwaves - Chrisp, Peter (Brainwaves series., 2010)
A Brainwave and his globetrotting pals serve as traveling companions through time to experience history's journeys of discovery, meeting famous explorers and sharing their stories.